SCIENTIFIC RESEARCH AT THE CHISINAU STATE INSTITUTE OF MEDICINE (1945–1990) - Ion Valer XENOFONTOV (Akademos: Revista de Ştiinţă, Inovare, Cultură şi Artă, 2020)
Scientific activity, one inherent in higher education institutions, was appreciate from the beginning as a basic one in the complex functioning of the Chisinau State Institute of Medicine. In 1949, the Institute obtained the right to defend doctoral theses and to confer scientific doctoral degrees in medical sciences, and in 1964 – to conferring the title of doctor habilitat in medicine. Based on non published materials selected in public and private archives, and the literature, in this article the authors analyzes the complex scientific activity of Chisinau State Institute of Medicine in 1945–1990 period of time. Unlike other higher education institutions created in Moldavian SSR, the one in medical field had specific features. It was founded on the basis of scholars with a high pedagogical and scientific experience from prestigious scientific-didactic and clinical centers, being, thus, perpetuated the tradition of important medical scientific schools from Russian Empire and Soviet Union.